Strategic Marketing for Indonesia Local Game Company To Increase Product Attractiveness - Prayogo Dwiharyono; Nila Hidayat; Yosman Bustaman (ADI Publisher, 2020)
The current games industry growth in Indonesia is quite good and is growing rapidly to date. The value of the game industry in Indonesia already reached 800 million USD or around Rp.11 Trillion based on the survey in 2017. However, even though the growth of the games industry is high, most of the market is still untapped by local game companies. Because of that, the local game companies in Indonesia need to develop a strategy to get more market share in the local game market. This research aims to measure the influence of the 4P marketing mix in the Indonesia games market, and formulate a suitable strategy to increase the product attractiveness based on the Indonesia game market characteristic. The variable for this research is the 4P marketing mix combined into a marketing strategy and product attractiveness. The research is done through qualitative interview method, and quantitative method through survey to 75 respondents with SPSS as the data analysis tool for the results. The study finds that the marketing strategy has low influence on the product attractiveness variable, also, between the 4P marketing mix, the promotion has the highest relation to the product attractiveness compared to price, place/position, or product.